PENERAPAN METODE SEL BELAJAR DALAM PEMBELAJARAN MEMBACA INTENSIF TEKS PROSEDUR KOMPLEKS - Herawati Murti Gustiani (Sekolah Pascasarjana Universitas Pendidikan Indonesia, 2016)
Text complex procedures are one of the learning material in Curriculum 2013. One of the skills that must be mastered student is reading the text of a complex procedure. In fact there are many students who are lazy to read. Students find it difficult to conclude the text content of complex procedures that they read. One cause of the problem is the method in which the teacher is monotonous and does not stimulate students to be active during learning. Learning Cells are cooperative learning method that requires students active during learning. The purpose of this study to determine whether there is a significant difference between the ability to read text intensive complex procedure of students before and after using the Cell study. The method used is a quasi-experimental research design control group pre-test-post-test. The sampling technique used purposive sampling study. This research data in the form of pre-test-post-test results text capabilities complex procedure experimental class and control class and the results of observation. This study is an attempt to apply the 2013 Curriculum Assessment includes the student's attitude when the treatment is done. Research results through hypothesis testing revealed the existence of differences in the ability to read text intensive complex procedures significantly between learning method with learning Learning Cells that do not use that method.Keywords: text complex procedures, cell method learning.